The Prevalence of Pulmonary Hypertension Among Maintenance Dialysis Patients With ESRD and Its Associated Factors: A Retrospective Study - Zhang, Ying; Ding, Xiao-Han; Rao, Rongsheng; Wang, Yiqin; Pang, Fang; Tang, Sha; Nie, Ling; Bian, Shi-Zhu (Frontiers in Medicine, 2020)
Aim: To determine the prevalence of pulmonary hypertension (PH) and its associated factors among end-stage renal disease (ESRD) patients who underwent maintenance dialysis. Methods: A total of 491 patients received echocardiography examinations and underwent pulmonary artery systolic pressure (PASP) assessments. A subgroup of 283 patients were subjected to plasma creatinine (Cr) and blood urea nitrogen concentration (BUN) tests, routine blood examinations and electrolyte analysis. First, we compared the differences in echocardiographic, Cr and BUN, blood routine and electrolyte parameters between PH and non-PH groups. The correlations between PASP and the parameters mentioned above were also analyzed. Furthermore, univariate and adjusted logistic regression analyses were performed to identify the independent associated factors. Results: The incidence of PH among ESRD patients who were treated with maintenance dialysis was 34.6%. Most of the echocardiographic parameters, including end-diastolic internal diameters of the left atrium, left ventricle, right atrium and pulmonary artery, as well as interventricular septum mobility, left ventricular posterior wall mobility, fractional shortening, stroke volume and left ventricle ejection fraction (LVEF), were associated with PH. Furthermore, Mg2+ (p = 0.037) and Cl- (p = 0.043) were significantly associated with PASP. However, after adjustments were made in the regression analysis, only internal diameters of the left atrium, right atrium and LVEF were independently associated with PH. Conclusion: PH is prevalent, with a relatively high incidence among ESRD patients who undergo maintenance dialysis. The sizes of the left and right atria as well as LVEF were independently associated with PH, but further cohort and basic mechanistic studies are needed to confirm this finding.